Interplay between lipid profiles, thyroid function, and gallstone disease: A clinical perspective - Vivek Nagappa; Akhila Bhandarkar (Journal of Family Medicine and Primary Care)
Background: New research points to a complicated relationship between gallstone disease (GSD), thyroid function, and lipid profiles. To better understand how to prevent and treat GSD, this study will look at how common thyroid abnormalities are among people with the diagnosis, as well as any dyslipidemias that may be present. Material and Methods: This is a cross-sectional observational study worked out at a tertiary care hospital in southern India’s Department of General Surgery. We enrolled 60 persons with a GSD diagnosis. We divided patients with only gallstones and gallstones with common bile duct stones and thyroid function was classified as euthyroid, subclinical hypothyroidism, or clinical hypothyroidism. Results showing triglycerides >150 mg/dL and total cholesterol >200 mg/dL were judged high in the lipid profile evaluation. Results: The majority of the cohort was between the ages of 51 and 60, and there were 61.6% females and 38.4% males. Subclinical hypothyroidism affected 13.33% of individuals, while 86.67% were euthyroid. We did not find any cases of clinical hypothyroidism. A total of 100% of individuals with subclinical hypothyroidism had dyslipidemia, while only 36.5% of euthyroid patients did. Elevated total cholesterol levels were shown to be significantly correlated with subclinical hypothyroidism (P < 0.05). The total cholesterol levels of obese people were also noticeably greater than those of normal-weight persons (P = 0.04). There was no discernible relationship between thyroid function or dyslipidemia, and gallstone type (alone vs. mixed with CBD stones). Conclusion: Knowing the status of thyroid function is essential to manage lipid abnormality in patients with gallstones even though there is no significant association with gallstones. Gallstone formation and lipid metabolism are both influenced by thyroid function status and its regulation. These results provide valuable insights for clinical practice in managing GSD.